Photon-counting CT versus energy-integrating detectors for cardiac imaging: a systematic review of evidence from in vivo human studies on image quality and radiation dose - Magnar Rønning; Elias Johansen; Albertina Rusandu (BMC Medical Imaging)
Abstract Background Computed tomography (CT) is central to cardiovascular diagnostics, with coronary CT angiography (CCTA) widely used for evaluating coronary artery disease (CAD) due to its high sensitivity and negative predictive value. However, conventional energy-integrating detector (EID) CT is limited by reduced contrast resolution and artifacts, especially in patients with heavy calcification or stents, which can impair diagnostic accuracy. Photon-counting CT (PCCT) is an emerging technology that directly converts X-ray photons into electrical signals, offering improved spatial resolution, contrast-to-noise ratio (CNR), and dose efficiency. While phantom studies have demonstrated its potential, clinical validation remains limited. This systematic review assesses image quality and radiation dose of PCCT versus EID in human in vivo cardiovascular imaging studies. Methods A systematic literature search was conducted in PubMed and Embase following PRISMA guidelines. Studies comparing PCCT and EID in cardiovascular imaging in human patients were included. Outcomes of interest were image quality parameters (CNR, SNR, artifacts), subjective image quality, diagnostic confidence, and radiation dose metrics. Results Eleven studies met the inclusion criteria, encompassing a range of cardiovascular applications including CCTA, stent assessment, and coronary calcium scoring. Across studies, PCCT consistently demonstrated the potential to improve diagnostic image quality at similar radiation doses, or to maintain the image quality while enabling significant reductions in radiation dose and, in some cases, contrast media volume. Artifact reduction, especially for blooming around calcifications, was frequently reported. However, variation in imaging protocols and outcome measures limited direct comparisons. Conclusion Current evidence from human in vivo studies supports that PCCT offers significant advantages in terms of image quality and radiation dose in cardiac CT examinations. Subjective image quality is particularly enhanced, while objective parameters remain influenced by technical factors and protocol selection. While findings are promising, especially for patients with complex coronary pathology, further large-scale, standardized studies are needed to confirm diagnostic and prognostic benefits in routine clinical practice.